Early Predictors of Child's Bully and Victim Statuses: A Longitudinal Investigation Using Parent, Teacher, and Student Reports From National Data - Natesan, Prathiba; Mitchell, Mary E.; Glover, Rebecca J. (Frontiers in Education, 2018)
Although bullying is known to have detrimental effects, less is known regarding how these bullies and victims develop within the contexts of their homes and schools, and how early childhood behaviors can predict later bullying/victimization statuses. Parent, teacher, and student reports from the Early Childhood Longitudinal Study – Kindergarten (ECLS-K) 1998-1999 cohort (N=11,715) representing a nationwide sample of children, were utilized to predict child’s bully and victim status in eighth grade (age 13-14) using data from seven collection points. Results indicated child characteristics from the earliest time points identified children at risk for becoming both bullies and victims, though familial characteristics were only able to predict bully status. Identifying these characteristics provides opportunities for early intervention in children’s lives, potentially preventing negative effects of bullying and victimization on academic, social, and emotional functioning. Implications for future research, including special considerations for individuals with internalizing behaviors, are discussed.